Investigation on Deicing Property of Steel Wool Fiber-Reinforced Asphalt Mixture by Induction Heating. (11th January 2020) - Yang, Fa; Li, Kehong; Xiong, Rui; Guan, Bowen; Zhao, Hua
Abstract : In order to effectively solve the traffic safety problem caused by snow and ice covering the pavement in winter, steel wool fibers with different length and content were adopted in asphalt mixture to investigate its deicing performance. The deicing principle of steel wool fiber asphalt mixture by induction heating was expounded. Effects of different ice thicknesses, output currents, and ambient temperatures for asphalt mixture deicing performance were studied using an indoor-simulated induction heating deicing test. The deicing mechanism of steel wool fiber asphalt mixture by induction heating was analyzed. Grey relation entropy analysis between the average melting ice rate and the influencing factors was determined. The results show that the average ice melting rate of the asphalt mixture increases with the increase in steel wool fiber length and content. The steel wool fiber asphalt mixture heated by electromagnetic induction obtains satisfactory result. The average melting ice rate of asphalt mixture containing 6% steel wool fiber with a length of 3 mm can reach 0.50°C·s −1 at an ambient temperature of −5°C. The thinner the ice and the higher the ambient temperature, the higher the average melting ice rate. The output current is positively correlated with the average melting ice rate. The degree of influence of the five influence factors on the average melting ice rate is ranked in order as follows: fiber content, fiber length, output current, ambient temperature, and ice layer thickness.